2020
DOI: 10.3389/fonc.2020.01779
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Evaluation and Comparison of 14 Diagnostic Markers for Nasopharyngeal Carcinoma: A Meta-Analysis

Abstract: The aim of the present study was to collect published studies and compare the diagnostic accuracy of different markers for nasopharyngeal carcinoma (NPC). We systematically searched PubMed/MEDLINE, EMBASE, Cochrane Library, CNKI, and Wanfang for relevant studies until April 29, 2020. The revised Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) tool was used to evaluate the methodological quality of the studies. The sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 113 publications
0
8
0
1
Order By: Relevance
“… 18 Antibodies against lytic EBV proteins including capsid antigen (VCA), BZLF1 transcription activator protein (Zta) and early antigen (EA) have shown great potential to stratify NPC cases and controls (area under the curve = 0.90–0.93). 19 , 20 Individuals with elevated levels of immunoglobulin (Ig)A antibodies against lytic EBV proteins have a 20‐ to 30‐fold higher risk of NPC. 21 Longitudinal cohort studies have revealed that the elevated IgA level precedes the occurrence of NPC by 1–15 years.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Antibodies against lytic EBV proteins including capsid antigen (VCA), BZLF1 transcription activator protein (Zta) and early antigen (EA) have shown great potential to stratify NPC cases and controls (area under the curve = 0.90–0.93). 19 , 20 Individuals with elevated levels of immunoglobulin (Ig)A antibodies against lytic EBV proteins have a 20‐ to 30‐fold higher risk of NPC. 21 Longitudinal cohort studies have revealed that the elevated IgA level precedes the occurrence of NPC by 1–15 years.…”
Section: Introductionmentioning
confidence: 99%
“…30 Nevertheless, serum EBV Zta antibody is not popular for the identification of NPC in clinical practices. 31 Heat shock protein (HSP), also termed stress protein, is a class of proteins that are highly expressed in cells in response to physicochemical stimuli. 32 Based on the molecular weight, HSPs are classified into HSP110, HSP90, HSP70, HSP60 and small HSPs (sHSPs).…”
Section: Discussionmentioning
confidence: 99%
“…Eine EBV-Assoziation besteht darüber hinaus mit verschiedenen epithelialen Neoplasien, darunter fast allen Nasopharynxkarzinomen (NPC) und 10 % der Magenkarzinome [1]. Beim Monitoring des NPC haben sich EBV-spezifische Antikörper und Viruslast im Blut als hilfreich erwiesen [47].…”
Section: Malignome Und Lymphoproliferative Erkrankungenunclassified